PELATIHAN PENERAPAN TEKNOLOGI SIRKULASI BUKU BERBASIS APLIKASI SLiMS PADA PROGRAM TAMAN BACAAN MASYARAKAT (TBM) - Laksono, Bayu Adi; Hamdan, Ahmad; Novitasari, Nastiti; Mumu (CV Bayfa Cendekia Indonesia Bekerjasama dengan Jurusan/Program Studi Pendidikan Masyarakat FKIP Universitas Siliwangi, 2023)
The training on the implementation of book circulation technology based on the SLiMS application in Community Reading Parks (TBM) aims to enhance the effectiveness and efficiency of book circulation processes in TBMs and streamline the management of book and member data in TBMs. This training involves the target of improving participants' proficiency in using the SLiMS application and optimizing the use of technology in book circulation processes at TBMs. The method employed for this training includes face-to-face instruction and hands-on practice with the SLiMS application. The training will be conducted in several stages, including the utilization of technology in book circulation processes at TBMs, introduction to the SLiMS application and its features, hands-on practice with the SLiMS application, and evaluation and discussion. Various instructional media, such as presentations, group discussions, and practical exercises, will be utilized in the training. Periodic evaluations will ensure that participants have comprehended the material and can apply it effectively in the book circulation processes at TBMs. In conclusion, the training on the implementation of book circulation technology based on the SLiMS application in Community Reading Parks (TBM) aims to enhance the effectiveness and efficiency of book circulation processes at TBMs and facilitate the management of book and member data. The training will utilize face-to-face instruction and practical application of the SLiMS application, with the expectation that participants will gain a thorough understanding of and effectively apply technology in the book circulation processes at TBMs.